Energy System Assessment in Survivors of Breast Cancer. Issue 3 (10th February 2020) - Cuesta-Vargas, Antonio Ignacio; Buchan, Jena; Pajares, Bella; Alba, Emilio; Trinidad-Fernández, Manuel; Ruiz-Medina, Sofia; García-Almeida, José Manuel; Ríos-López, María José; Roldán-Jiménez, Cristina
Abstract: Background: Survivors of breast cancer commonly report functional limitations, including cancer-related fatigue (CRF) and decreased aerobic capacity. One key gap is addressing the 3 energy systems (aerobic, anaerobic lactic, and alactic), requiring assessment to establish a baseline exercise intensity and duration. Objective: This study examined the feasibility of energy system–based assessment, also providing descriptive values for assessment performance in this population. Design: This was a cross-sectional study. Methods: Seventy-two posttreatment survivors of breast cancer were recruited. Following a baseline musculoskeletal assessment, women attempted 3 energy system assessments: submaximal aerobic (multistage treadmill), anaerobic alactic (30-second sit-to-stand [30-STS]), and anaerobic lactic (adapted burpees). Heart rate (HR) and rating of perceived exertion (RPE) were recorded. Secondary outcomes included body composition, CRF, and upper- and lower-limb functionality. Results: Seventy of 72 participants performed the 30-STS and 30 completed the adapted burpees task. HR and RPE specific to each task were correlated, reflecting increased intensity. Women reported low-moderate levels of CRF scores (3% [2.1]) and moderate-high functionality levels (upper-limb: 65.8% [23.3]; lower-limb: 63.7% [34.7]). Limitations: All survivors of breast cancer had relatively low levels of CRF and moderate functioning. Additionally, on average, participants were classified as "overweight" based on BMI. Conclusion: This study is the first to our knowledge to demonstrate feasibility of energy system assessment in survivors of breast cancer. Using a combination of HR and RPE, as well as baseline assessment of each energy system, clinicians may improve ability to prescribe personalized exercise and give patients greater ability to self-monitor intensity and progress.